Perencanaan Ruang Usaha PKL di Kompleks Terminal Dhaksinarga Wonosari Berbasis Komunitas - Damanik, Imelda Irmawati; Raniasta, Yohanes Satyayoga; Kinanthi, Maria (Jurnal Atma Inovasia, 2024)
The economic growth of the city is closely related to informal activities, one of which is street vendors (PKL - "Pedagang Kaki Lima"). PKL activities generally seek strategic urban spaces to conduct informal trading businesses. The Pedagang Kaki Lima community in Gunung Kidul has been given the opportunity to develop their trading activities in the Dhaksinarga terminal complex in Wonosari city. The existing condition of the Dhaksinarga terminal prompted the PKL vendors to contact the Urban and Settlement Environment Laboratory of the Faculty of Architecture and Design at UKDW to assist in planning the PKL business spaces with a people-oriented concept. In this community engagement (PkM) activity, the design process is carried out using a community-based design approach, with the aim of producing a design that suits the space needed for the unique trading activities of PKL vendors in Gunung Kidul, who are part of the PPKL-Gunung Kidul association. Moreover, considering that this business space is located within the Dhaksinarga terminal complex managed by the Department of Transportation, all design efforts must align with the public service function of the Dhaksinarga Terminal. This PkM process will be a collaboration between the community (PPKL-Gunung Kidul), academia (Urban and Settlement Environment Laboratory, UKDW), and the government (Department of Transportation), requiring mapping to ensure that all parties benefit from the PKL business space design activity.